Das Thema patristischer Ethik: Versuch einer Annäherung durch Distanz am Beispiel der Briefe des Augustinus von Hippo - Nunn, Christopher Alexander (Journal of ethics in Antiquity and Christianity, 2022)
Ethics can be defined completely differently depending on which topics are subsumed under it. This makes it difficult to describe the ethics of a patristic author when prevailing concepts of ethics thematically limit the analysis. The digitisation of Augustine's works makes him an ideal candidate for a patristic Distant Reading Experiment to approach this problem. With the help of various distant reading methods, letters will be found that can provide information about his general understanding of ethics in practice. Furthermore, the possibilities and limits of such an analytical approach for the study of late antiquity will be explored